MANAJEMEN REDAKSI RIAUTERKINI.COM DALAM MENGHADAPI PERSAINGAN MEDIA ONLINE DI RIAU - Ula, Aristra Risqunal; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Today the internet is nothing new for the community. It is efficient, inexpensive, andquick to make people make it part of a necessity. It is also an impact on the world of journalismthat naturally follow the development of this technology. Many online news stand and thismakes the competition to be competitive in the world press. In Riau, there were 200 online mediaand that number could continue to grow given the business of making easy online media. So inthis case Riauterkini.com which is the oldest online media in Riau should be able to face thiscompetition. Through the editorial management is used, it will be seen how Riauterkini.comdealing this competition. So the purpose of this research also want to know the applicationfunctions Riauterkini.com editorial management in the face of online media competition in Riau.This research used a qualitative method with descriptive approach undertaken ineditorial news sites www.riauterkini.com, 33th Soekarno Hatta Street, Pekanbaru. The object ofthis study is the editorial management Riauterkini.com, with research subjects include thegeneral leader, editorial director, two editors, two journalists, technicians in IT, andadministration/general staff. Data collection techniques used were interviews, observation, anddocumentation.The results of this study describes how the application of planning, organizing, actuating, andcontrolling (POAC) on editorial Riauterkini.com as efforts in the deal of online media in Riau.Riauterkini.com implement the planning function with the editorial meeting that the projectedmeeting. Where Riauterkini.com focus is to maintain its position in order to remain strong andsurvive in the realm of online news industry competition. Then organizing function,Riauterkini.com using a system of division of labor that is very simple to use dual system but putforward in the deployment position of journalists in all regions of coverage. Further agitationapplied Riauterkini.com editorial controlled by the editorial director to exercise that begins withcoverage of news material, which focuses on the accuracy of the data, news writing, to editingthe news in order to avoid writing mistakes, including procurement effort photo/picture news.Then the application of supervisory functions discussed in the evaluation meeting that includesthe target of good writing, audience target, and election news theme. The entire series of theseapplication functions is a form of editorial managerial done in order to face the competition ofonline media in Riau.Keyword: editorial management, competitive, online media